1991
DOI: 10.1128/jb.173.21.7046-7049.1991
|View full text |Cite
|
Sign up to set email alerts
|

Purification and N-terminal amino acid sequences of Chlamydia trachomatis histone analogs

Abstract: DNA-binding proteins specific to Chlamydia trachomatis elementary bodies have been described and recently characterized as procaryotic histone analogs. I have developed an affinity purification procedure for the 18-kDa histone analog, Hcl, based on its affinity for polyanions. The availability of highly purified Hcl has allowed for determination of its N-terminal amino acid sequence and should prove useful in studies of its biological function. The variable C. trachomatis histone analog not obtained by this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…C. trachomatis nucleoids were isolated from EBs by extraction with 2% Zwittergent 3-14 (Calbiochem) for 1 h at room temperature with rotation. This procedure yielded structures consisting of the nucleoid surrounded by the freely permeable disulfide-linked outer membrane complex (19). Nucleoid complexes were pelleted at 15,000 ϫ g for 5 min and washed at least three times with PBSE (50 mM sodium phosphate, pH 7.5͞150 mM NaCl͞1.5 mM EDTA) Deproteinated E. coli Extract.…”
Section: Methodsmentioning
confidence: 99%
“…C. trachomatis nucleoids were isolated from EBs by extraction with 2% Zwittergent 3-14 (Calbiochem) for 1 h at room temperature with rotation. This procedure yielded structures consisting of the nucleoid surrounded by the freely permeable disulfide-linked outer membrane complex (19). Nucleoid complexes were pelleted at 15,000 ϫ g for 5 min and washed at least three times with PBSE (50 mM sodium phosphate, pH 7.5͞150 mM NaCl͞1.5 mM EDTA) Deproteinated E. coli Extract.…”
Section: Methodsmentioning
confidence: 99%
“…RESULTS Molecular cloning of hctB. The marked similarity of the N-terminal amino acid sequences of purified Hc2 proteins of serotypes L2, D, and B (15) and that deduced for the 26-kDa KARP of C trachomatis MoPn (27) strongly suggested that these proteins were homologous. Recombinant Xgtll bacteriophage encoding Hc2 of C. trachomatis L2 were identified by high-stringency in situ plaque hybridization using a cloned DNA probe internal to the coding sequences for the KARP of strain MoPn.…”
mentioning
confidence: 98%
“…Immunoblot analysis of purified preparations of L2 RBs and EBs by using an Hc2-specific monoclonal antibody further confirmed that Hc2 is undetectable at the RB stage of chlamydial development (5). This family of proteins includes the lysine-and alanine-rich protein (KARP) of strain MoPn (27) as well as other proteins described previously (14)(15)(16), which in. serotype L2 have an apparent molecular mass of 32 kDa in sodium dodecyl sulfate (SDS)-polyacrylamide gels.…”
mentioning
confidence: 99%
“…Shown here is a silver-stained SDS-PAGE profile of fractions of a whole-cell lysate of C. burnetii (9mi/II), an octylglucopyranoside extract (OGP-Sup), and fractions eluted with increasing NaCl concentrations. C. burnetii was extracted with a mixture containing 100 mM sodium carbonate, 10 mM EDTA, and 1% octylglucopyranoside (pH 10.5), and Hq1 was purified by heparin-agarose affinity chromatography essentially as described previously (6). Hq1 bound heparin with high affinity and was eluted at a NaCl concentration of 1 M. The N-terminal amino acid sequence of the purified Hq1 was determined with an Applied Biosystems model 470A protein sequencer.…”
Section: Figmentioning
confidence: 99%
“…The affinity of the presumed histone-like proteins of C. burnetii for DNA suggested that they may be amenable to purification schemes developed for isolation of chlamydial histones. C. burnetii was extracted with a mixture of 100 mM sodium carbonate, 10 mM EDTA, and 1% octylglucopyranoside (pH 10.5), and Hq1 was purified by heparin-agarose affinity chromatography essentially as described previously (6). Hq1 bound heparin with high affinity and was eluted at a NaCl concentration of 1 M (Fig.…”
mentioning
confidence: 99%